The neutron halo structure of 17B studied with the relativistic Hartree-Bogoliubov theory - 姬娟霞 李加兴 韩瑞 王建松 胡强 (Chinese physics C, 2012)
The properties of neutron-rich boron isotopes are studied in the relativistic continuum Hartree-Bogoliubov theory in coordinate space with NL-SH,PK1 and TM2 effective interactions.Pairing corrections are taken into account by a density dependent force of zero range.The binding energies calculated for these nuclei agree with the experimental data quite well.The neutron-rich nucleus 17 B has been predicted to have a two-neutron halo structure in its ground state.The halo structure of 17 B is reproduced in a self-consistent way,and this halo is shown to be formed by the valence neutron level 2s 1/2.